Evaluation of Speech Skills and Social Interaction in Preschool Age Children With ASD in the Conditions of Psychological and Pedagogical Support of Kindergarten - Irina Nigmatullina; Veronika Vasina; Yana Mukhamedshina (ARPHA Proceedings, 2022)
The predictors of successful socialization of children with autism spectrum disorders (ASD) are a high degree of development of verbal and social interaction skills. The existing system of psychological and pedagogical support from the preschool period should aim at effectively overcoming the above difficulties.The research presents the results of a two-year study of 52 organized preschoolers aged 3 to 8 years with ASD under the VB-MAPP Skills and Social Interaction Assessment Program. The results showed insignificant dynamics in the development of verbal and social interaction skills in preschoolers with ASD attending kindergartens. Questioning of caregivers who raise children with ASD confirmed their dissatisfaction with the existing system of support of preschoolers with ASD in the region. The results indicate the insufficient effectiveness of the existing system of psychological and pedagogical support of children in preschool educational institutions and actualize the issue of implementing the system of comprehensive support of children with ASD for their successful socialization.